Bound for Canaan : the epic story of the underground railroad, America's first civil rights movement - Bordewich, Fergus M. (Amistad, 2006)
With a historian's grasp of events and a novelist's instinct for story, Bordewich focuses on the 60 years leading up to the Civil War. Its beginnings can be traced to a band of abolitionists who created what became known as the Underground Railroad.